Intraosseous fluid resuscitation in meningococcal disease and lower limb injury - Suparna Dasgupta; Stephen D.R. Playfor (MDPI AG, 2010)
We set out to review the recent incidence of extravasation and compartment syndrome in children with meningococcal disease admitted to our Paediatric Intensive Care Unit (PICU) who had been resuscitated with intraosseous (IO) needles. Over a 12-month period, 18 children were admitted to PICU with meningococcal sepsis. Four of these children were resuscitated with IO needles and 2 developed serious complications as a result of extravasation and compartment syndrome. Clinical practice guidelines for children with severe sepsis advocate aggressive early fluid resuscitation therapy. We have identified extravasation and lower limb injury as a potential issue of increasing concern with appropriate aggressive IO fluid resuscitation in severe septic shock in children. Powered IO access systems such as the EZ-IO system offer advantages in terms of placement speed, accuracy and bone entry site profile at minimal extra financial cost.